2021
DOI: 10.1177/1753193420982192
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic study of fibrous structures attached to the volar ulnar corner of the radius: implications in the volar rim fracture

Abstract: This study aimed to clarify the bone and soft tissue morphological features at the volar ulnar corner of the radius. Micro-computed tomography, macroscopic and histological analyses were conducted using 12 cadaveric wrists, and in vivo MRI studies of the wrist were evaluated in five healthy volunteers. The volar ulnar corner of the distal radius has a protrusion volar to the sigmoid notch. The capsule elements of the radiolunate and radioulnar joints merge and this conjoined capsule attaches to the radius at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…A later study by Saka et al (2021) also showed fibers attaching to the sigmoid notch, which was located at the ulnar protrusion of the volar ulnar rim of the radius, connected with the dorsal side of the ulnar styloid process. Those authors also showed that the attachment at the sigmoid notch could not be separated into a separate radioulnar‐ and short radiolunate ligament and therefore was termed the volar ulnar capsule (Saka et al, 2021).…”
Section: Tfcc Componentsmentioning
confidence: 88%
See 2 more Smart Citations
“…A later study by Saka et al (2021) also showed fibers attaching to the sigmoid notch, which was located at the ulnar protrusion of the volar ulnar rim of the radius, connected with the dorsal side of the ulnar styloid process. Those authors also showed that the attachment at the sigmoid notch could not be separated into a separate radioulnar‐ and short radiolunate ligament and therefore was termed the volar ulnar capsule (Saka et al, 2021).…”
Section: Tfcc Componentsmentioning
confidence: 88%
“…The terminology used in the anatomical studies for this structure showed a large variety with articular disc (proper) ( n = 9) (Benjamin et al, 1990; Chidgey et al, 1991; Ekenstam & Hagert, 1985; Ishii et al, 1998; Kleinman & Graham, 1998; Ohmori & Azuma, 1998; Rein et al, 2015; Semisch et al, 2016; Shigemitsu et al, 2007), disc/disk proper ( n = 6) (Horiuchi et al, 2020; Nakamura et al, 1996; Nakamura et al, 2001; Nakamura & Makita, 2000; Nakamura & Yabe, 2000; Saka et al, 2021), triangular fibrocartilage ( n = 4) (Bednar et al, 1991; Mikic, 1978; Viegas & Ballantyne, 1987; Zhan, Li, et al, 2017), or central disk ( n = 1) (Totterman & Miller, 1995). One study referred to the ulnar attachment fibers of the disc with the term “triangular ligament” (Zhan, Li, et al, 2017).…”
Section: Tfcc Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Nimura et al ( 2012 ) concluded that the conventional anatomical study overestimated the attachment width of the rotator cuff, and the capsular attachment of the shoulder joint occupied a substantial area of the greater tuberosity by the precise discrimination between the actual cuff insertion and capsular attachment. In other articular systems apart from the shoulder joint, such as the elbow, wrist, thumb metacarpophalangeal joint, knee, and ankle, many anatomical studies have also shown that the capsular attachment is not always linear, and its width varies according to the bony location (Amaha et al 2019 ; Nasu et al 2018 ; Nimura et al 2014 ; Saka et al 2021 ; Sato et al 2018 ; Shimura et al 2016 ). Therefore, these anatomical studies suggest that the width of the capsular attachment is wider than previously reported in most articular systems.…”
Section: Capsular Attachment On the Anterosuperior Acetabular Marginmentioning
confidence: 99%
“…[1][2][3] The short radiolunate ligament and the volar distal radioulnar ligament originate from the volar margin of the lunate facet. 4 The VLF fragment bears more load than that of the scaphoid fossa, and this force is transmitted across the volar margin of the lunate fossa. 1 O'Shaughnessy et al reported that the VLF fragment size, especially the length of its volar cortex, is of utmost importance for secure internal fixation.…”
mentioning
confidence: 99%